Lullaby Town (Elvis Cole/Joe Pike novels, 3, 1, 2008)
Peter Alan Nelsen is a super successful movie director who is used to getting what he wants. And what he wants is to find the wife and infant child he dumped on the road to fame. It's the kind of case that Cole could handle in his sleep, except that when Cole actually finds Nelsen's ex wife, everything takes on nightmarish proportions a nightmare which involves Cole with a nasty New York mob family and a psychokiller who is the son of the godfather. When the unpredictable Nelsen charges in, an explosive situation blows sky high.

Lullaby Town (#3): Elvis Cole and Joe Pike (Elvis Cole/Joe Pike novels, 3, 1, 1992)
Lullaby Town is Chelam, Connecticut, where L.A. shamus Elvis Cole goes in search of Karen Shipley, divorced ten years earlier by boyish filmmaker Peter Alan Nelsen, who's since developed deep pocketsand a conscience of sorts.

The Monkey's Raincoat (Elvis Cole/Joe Pike novels, 1, 1, 2019)
"Meet Elvis Cole, L.A. Private Eye.... He quotes Jiminy Cricket and carries a .38. He's a literate, wisecracking Vietnam vet who is determined to never grow up. When quiet Ellen Lang enters Elvis Cole's Disney-Deco office, she's lost something very valuable--her husband and her young son. The case seems simple enough, but Elvis isn't thrilled. Neither is his enigmatic partner and firepower, Joe Pike. Their search down the seamy side of Hollywood's studio lots and sculptured lawns soon leads them deep into a nasty netherworld of drugs, sex--and murder. Now the case is getting interesting, but it's also turned ugly. Because everybody, from cops to starlets to crooks, has declared war on Ellen and Elvis. For Ellen, it isn't Funtown anymore. For Elvis, it's just a living... He hopes." -- Amazon.

Stalking the angel (Elvis Cole/Joe Pike novels, 2, 1, 2008)
L.A.-based sleuth Elvis Cole is hired by a ruthless hotel magnate to find a priceless Japanese manuscript and finds himself trapped in a web of Japanese organized crime, treachery, and murder.

Free fall (Elvis Cole/Joe Pike novels, 4, 1, 2019)
Elvis uncovers a world of corrupted cops in the LAPD, and his investigation takes him to the heart of the war zone in South Central Los Angeles where he must confront street gangs and conspiracies of silence.

Free fall (#4): Elvis Cole and Joe Pike (Elvis Cole/Joe Pike novels, 4, 1, 1993)
L.A. detective Elvis Cole aids a woman distressed by her fiance's involvement in illicit police work in this Edgar nominee.

Voodoo River (Elvis Cole/Joe Pike novels, 5, 1, 1995)
"Robert Crais has established Elvis Cole, his wisecracking private eye with a tough exterior but a soft heart, in the consciousness of mystery readers and reviewers everywhere. In Voodoo River, Elvis Cole returns in his most exciting adventure yet. Hired to uncover the past of Jodi Taylor, an actress in a hit television series, Elvis leaves his native Los Angeles to journey to deepest Louisiana to search for Jodi's biological parents. Soon he discovers the real reason he's been sent there - but not before run-ins with an amazing cast of characters, including a crazed, Raid-spraying housewife; a Cajun thug who looks like he's been built out of spare parts; and a menacing, hundred-year-old river turtle named Luther."--BOOK JACKET.

Voodoo River (#5): Elvis Cole and Joe Pike (Elvis Cole/Joe Pike novels, 5, 1, 1995)
Description Not Provided

Sunset express (Elvis Cole/Joe Pike novels, 6, 1, 1996)
Elvis Cole is back on his own turf in Los Angeles, and embroiled in a controversial high-profile murder case. A wealthy restaurateur is accused of murdering his wife, and his hot-shot defense attorney hires Elvis to find proof that police detective Angela Rossi fooled around with the evidence. Rossi had been cleared of an earlier charge of planting evidence to convict a counterfeiter, but her career was damaged and she's rumored to be willing to do anything to get it back on track - even if it means framing an innocent man. Yet as Elvis investigates Rossi for the defense team, he begins to be more suspicious of the media-loving lawyers than the cops. As the investigation continues, Elvis is visited by Lucy Chenier, the Louisiana lawyer he'd met several months ago. Lucy is in Los Angeles for a business trip, and as she and Elvis spend more time together, their mutual attraction grows. As the fireworks ignite, Elvis and Lucy are drawn deeper into the intrigue and dangers surrounding the case of the missing woman.

Sunset express (#6): Elvis Cole and Joe Pike (Elvis Cole/Joe Pike novels, 6, 1, 1996)
Prominent restaurateur Teddy Martin is facing charges in his wife's brutal murder. But he's not going down without spending a bundle of cash on his defense. His hotshot attorney hires P.I. Elvis Cole to find proof that Detective Angela Rossi tampered with the evidence.

Indigo slam (#7): Elvis Cole and Joe Pike (Elvis Cole/Joe Pike novels, 7, 1, 1997)
Los Angeles private detective Elvis Cole has trouble coming at him from all sides when his girlfriend Lucy's ex-husband shows up at his office making threats, and his search for a dead-beat dad turns up a mafia-connected counterfeiter.

Indigo slam: an Elvis Cole novel (Elvis Cole/Joe Pike novels, 7, 1, 1997)
Seattle PI Elvis Cole is hired by three children who want to make sure their father is still alive. He went into hiding, pursued by Russian counterfeiters on whom he squealed.

L.A. requiem (Elvis Cole/Joe Pike novels, 8, 1, 2009)
A reckoning has come to the City of Angels ... Karen Garcia is missing and her father doesn't trust the cops he wants someone he knows on the case so he enlists the help of Elvis Cole and Joe Pike. It seems that Karen is the latest victim of a distinctive serial killer and the police are determined to pin her death, and four others, on the witness who found her body. Cole doesn't believe the man has the guts to murder, and with his partner and the police at each other's throats, it's down to him to find the connection that will reveal the killer. But nailing the murderer means choosing between the two people he cares most about ...

L.A. requiem (#8): Elvis Cole and Joe Pike (Elvis Cole/Joe Pike novels, 8, 1, 1999)
Ex-cop Joe Pike and his partner, private detective Elvis Cole run afoul of the LAPD's elite Robbery-Homicide Division when they are hired to monitor the police investigation into the death of Joe's former lover, Karen Garcia.

The Last Detective (Elvis Cole/Joe Pike novels, 9, 1, 2004)
When the son of his long-time girlfriend, Lucy, goes missing, Elvis Cole finds himself encumbered by his personal demons, the dark secrets of his childhood, and long-supressed memories of his service in Vietnam.

The Forgotten Man (Elvis Cole/Joe Pike novels, 10, 1, 2005)
A man dying of a gunshot wound tells the police he's the father of Elvis Cole. Not having known his father, Elvis begins a search for the dead man's identity. As the investigation goes forward, a psychopath connected to the unidentified man comes to believe that Elvis is hunting him. The man, a merciless killer, goes on the attack to find Elvis before Elvis can find him.

The Watchman (Elvis Cole/Joe Pike novels, 11, 1, 2007)
Larkin Conner Barkley lives like the City of Angels is hers for the taking. Young and staggeringly rich, she speeds through the city during its loneliest hours, blowing through red after red in her Aston Martin as if running for her life. Until out of nowhere a car appears, and with it the metal-on-metal explosion of a terrible accident. Dazed, Larkin attempts to help the other victims. And finds herself the sole witness in a secret federal investigation. For maybe the! first time in her life, Larkin wants to do the right thing. But by agreeing to cooperate with the authorities, she becomes the target for a relentless team of killers. And when the U.S. Marshals and the finest security money can't protect her, Larkin's wealthy family 'turns to the one man money can't buy - Joe Pike. Pike lives a world away from the palaces of Beverly Hills. He's an ex-cop, ex-Marine, ex-mercenary who owes a bad man a favor, and that favor is to keep Larkin alive.

The watchman (#11): Elvis Cole and Joe Pike (Elvis Cole/Joe Pike novels, 11, 1, 2007)
As the subtitle suggests, Joe Pike, the intriguing, enigmatic partner of L.A. PI Elvis Cole, takes center stage in this intense thriller from bestseller Crais (The Two Minute Rule). To pay back an old debt, Pike is coerced into protecting Larkin Barkley, a hard-partying young heiress whose life is in danger after a "wrong place wrong time" encounter that quickly escalates and spins out of control. The enemy is shadowy, violent and relentlessb́ut the fierce, focused Pike, one of the strongest characters in modern crime fiction, is equal to the challenge. The breathless pace and rich styling are sure to appeal to readers of hard-boiled fiction in general, but since up to now Pike has mostly remained in the background, some fans of the Elvis Cole series (The Forgotten Man, etc.) may find the explicit picture that emerges of Pike at odds with the image they've constructed for themselves.

Chasing darkness: an Elvis Cole novel (Elvis Cole/Joe Pike novels, 12, 1, 2009)
As police evacuate a fire-threatened Los Angeles neighborhood, they discover the corpse of an apparent suicide. More gruesome is what they find in his lap: a photo album of seven murdered women. The suicide is identified as a former suspect in one of the murders. Lionel Byrd had been tried for the murder of Yvonne Bennett. It was Elvis Cole's discovery of an exculpatory videotape that allowed Byrd to walk free. But the discovery of the album shows that Yvonne Bennett was the fifth of the seven victims. Elvis can't help but wonder if he cost two more women their lives.

The first rule: a Joe Pike novel (Elvis Cole/Joe Pike novels, 13, 1, 2009)
The organized criminal gangs of the former Soviet Union are bound by what they call the thieves' code. The first rule is this: A thief must forsake his mother, father, brothers, and sisters. He must have no family-no wife, no children. We are his family. If any of the rules are broken, it is punishable by death. Frank Meyer had the American dream-until the day a professional crew invaded his home and murdered everyone inside. The only thing out of the ordinary about Meyer was that- before the family and the business and the normal life-a younger Frank Meyer had worked as a professional mercenary, with a man named Joe Pike. The police think Meyer was hiding something very bad, but Pike does not. With the help of Cole, he sets out on a hunt of his own-an investigation that quickly entangles them both in a web of ancient grudges, blood ties, blackmail, vengeance, double crosses, and cutthroat criminality, and at the heart of it, an act so terrible even Pike and Cole have no way to measure it. Sometimes, the past is never dead. It's not even past.